Beowulf and the Book of Swords: similarities and diﬀerences in scenes, features and epithets - Ogura, Michiko (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2019)
The Book of Swords, a Japanese analogue of Beowulf and a source of Rashohmon, resemble Beowulf in the structure of the three fi ghts but diff ers in contents. This paper gives common elements of fi ghting scenes and descriptions of the enemies to the heroes and shows how the two stories diff er. Keywords: Beowulf, The Book of Swords, Rashomon, Epic structure, Heroes, Comparative studies